Na⋯B bond in NaBH3- : An induced spin‐polarized bond. Issue 1 (15th November 2021) - Rincón, Luis; Mora, Jose R.; Rodriguez, Vladimir; Torres, F. Javier
Abstract: The nature of the Na⋯B bond, in the recently synthesized NaBH 3 - adduct, is analyzed on the light of the Na − propensity to polarize along the bond axis as a consequence of the electric field produced by the BH3 fragment. The observed induced polarization has two consequences: (i) the energetic stabilization of the Na −, and (ii) the split of its valence electrons into two opposite lobes along the bond axis. Additionally, an analysis of the electron localization is presented using the information content of the correlated conditional pair density that reveals a significant delocalization between one lobe of the polarized Na − anion and the BH3 fragment at the equilibrium distance. Our findings reported here complement previous works on this system. Abstract : Beyond electron‐share and ionic‐dative bond : the Na⋯B bond in NaBH 3 - bond is spin‐polarized in view of the large number of unpaired electrons in the Na and the BH3 fragments. Here, we emphasize that the spin‐polarization in the Na anion is induced by the BH3 . The delocalization of one electron in the BH3 produce a bond with a hight diradicaloid character.